The continuing arc toward phototropic enlightenment - Liscum, Emmanuel (J Exp Bot, 2020)
Phototropism represents a simple physiological mechanism—differential growth across the growing organ of a plant—to respond to gradients of light and maximize photosynthetic light capture (in aerial tissues) and water/nutrient acquisition (in roots). The phototropin blue light receptors, phot1 and phot2, have been identified as the essential sensors for phototropism. Additionally, several downstream signal/response components have been identified, including the phot-interacting proteins NON-PHOTOTROPIC HYPOCOTYL 3 (NPH3) and PHYTOCHROME SUBSTRATE 4 (PKS4). While the structural and photochemical properties of the phots are quite well understood, much less is known about how the phots signal through downstream regulators. Recent advances have, however, provided some intriguing clues. It appears that inactive receptor phot1 is found dispersed in a monomeric form at the plasma membrane in darkness. Upon light absorption dimerizes and clusters in sterol-rich microdomains where it is signal active. Additional studies showed that the phot-regulated phosphorylation status of both NPH3 and PKS4 is linked to phototropic responsiveness. While PKS4 can function as both a positive (in low light) and a negative (in high light) regulator of phototropism, NPH3 appears to function solely as a key positive regulator. Ultimately, it is the subcellular localization of NPH3 that appears crucial, an aspect regulated by its phosphorylation status. While phot1 activation promotes dephosphorylation of NPH3 and its movement from the plasma membrane to cytoplasmic foci, phot2 appears to modulate relocalization back to the plasma membrane. Together these findings are beginning to illuminate the complex biochemical and cellular events, involved in adaptively modifying phototropic responsiveness under a wide varying range of light conditions.